2015
DOI: 10.1515/jccm-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias in a Septic ICU Population: A Review

Abstract: Progressive cardiovascular deterioration plays a central role in the pathogenesis of multiple organ failure (MOF) caused by sepsis. Evidence of various cardiac arrhythmias in septic patients has been reported in many published studies. In the critically ill septic patients, compared to non-septic patients, new onset atrial fibrillation episodes are associated with high mortality rates and poor outcomes, amongst others being new episodes of stroke, heart failure and long vasopressor usage. The potential mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 57 publications
(104 reference statements)
1
25
0
Order By: Relevance
“…In general, patients with severe sepsis were more likely to be older in age, to have CHF, PVD, chronic obstructive pulmonary disease (COPD), DM and renal disease. Ischemic heart disease* 2,161,685 [7] 174,130 [10] CHF* 4,048,500 [14] 427,525 [24] PVD* 1,778,205 [6] 166,975 [10] Cerebrovascular disease* 1,952,330 [7] 144,150 [8] Chronic pulmonary disease* 6,493,627 [22] 495,285 [28] DM* 5,967,546 [21] 499,900 [28] DM with complications* 1,143,775 [4] 127,005 [7] Renal disease* 3,668,071 [13] 465,995 [27] Valvular heart disease* 1,717,610 [6] 131,640 [7] *Comparison between two groups done with Chi-square test. All P values significant at <0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients with severe sepsis were more likely to be older in age, to have CHF, PVD, chronic obstructive pulmonary disease (COPD), DM and renal disease. Ischemic heart disease* 2,161,685 [7] 174,130 [10] CHF* 4,048,500 [14] 427,525 [24] PVD* 1,778,205 [6] 166,975 [10] Cerebrovascular disease* 1,952,330 [7] 144,150 [8] Chronic pulmonary disease* 6,493,627 [22] 495,285 [28] DM* 5,967,546 [21] 499,900 [28] DM with complications* 1,143,775 [4] 127,005 [7] Renal disease* 3,668,071 [13] 465,995 [27] Valvular heart disease* 1,717,610 [6] 131,640 [7] *Comparison between two groups done with Chi-square test. All P values significant at <0.05.…”
Section: Resultsmentioning
confidence: 99%
“…As previous studies have shown, patients with moderate to severe sepsis have a greater likelihood of exhibiting various cardiac arrhythmias (5,6). The majority of these clinical studies were focused on the diagnosis, management, predictors and outcomes of new onset AF in the general intensive care patient population (7). However, studies performed to provide a comprehensive assessment of both atrial and ventricular arrhythmias in severe sepsis patients are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic dysfunction and tachycardia are associated with a poor outcome in septic shock 2 with mortalities in excess of 70%. 3 Bradycardia is relatively protective.…”
Section: Introductionmentioning
confidence: 99%
“…The review article published in this issue by Schwartz A et al [1] draws attention to the importance of cardiac arrhythmias and especially that of new-onset atrial fibrillation (AF) and the clinical outcome of septic patients. The incidence of this phenomenon varies in different reports, from 5.8% [2] to 31-40% [3][4].…”
mentioning
confidence: 99%
“…An increased inflammatory response also plays an important role in pathogenesis of cardiac arrhythmias and dysfunction in septic patients. Increased plasma levels of C-reactive protein, IL-6 and TNF-α may contribute to the onset of AF in septic patients [1,6].…”
mentioning
confidence: 99%